Contributions to the study of diversity, state and degree of vulnerability of vertebrate fauna in the "La Izvor" park, Bariera Sculeni, mun. Chisinau - CÎRLIG, Tatiana (Acta et Commentationes Exact and Natural Sciences, 2020)
The research of the urban ornithofauna was carried out within the institutional project, ,,The study of anthropogenic action on biodiversity, the physiological status of population Chisinau and the use of results in the formation of transdisciplinary competences in the educational process" carried out during the period 2015-2019. In a result of the research, 94 species of vertebrates belonging to 4 classes were determined: Mammalia, Aves, Reptilia and Amphibia. The Red Book of the Republic of Moldova includes 8 species of vertebrates from the research area, constituting 8.5%. Most of the vertebrate species reported in the research area are included in the lists of international nature conservation organizations.